Legal analysis of the application of Article 24 Paragraph (1) of The KUHPM to TNI soldiers who have been sentenced to prison - Davit Triyono (Annals of Justice and Humanity, 2023)
Purpose: Imprisonment is essentially a punishment of loss of freedom of movement for lawbreakers for a certain period of time or for life, which is determined by a judge and the decision has permanent legal force. During the loss of freedom of movement, the convict is placed in a Correctional Institution to be given guidance. Imprisonment is imposed on people who commit crimes in the form of crimes, both civil and military (TNI soldiers). The purpose of imposing a prison sentence is to educate prisoners, namely by creating a deterrent effect so that they repent and do not commit the act again. TNI soldiers who have been sentenced to imprisonment certainly have their own consequences that can be felt, both for the person concerned, their family, their unit and society in general. The imposition of imprisonment on TNI soldiers can have negative impacts, such as decreasing public trust in the TNI institution and damaging the image of the TNI as an institution that upholds discipline and law. Regarding the submission of UKP, it is certainly the right of every TNI soldier who has normatively met the requirements. How is the regulation and implementation of the reduction of service period for TNI soldiers who have been sentenced to prison in their subsequent career development and what is the ideal concept of regulating the service period for TNI soldiers who have been sentenced to prison in their subsequent career development. Research Methodology: The type that the author chose was legal synchronization, because the author saw a lack of synchronization between lower regulations (regulations in the TNI environment regarding the submission of UKP) and higher regulations, namely Article 24 paragraph (1) of the Criminal Code (Law Number 39 of 1947). Results: The TNI Commander's Regulation needs to explicitly regulate that the criminal period is not counted as part of the active service period, but the period before and after the criminal sentence is still counted as the total service period.